RETRACTED: The influence of digital finance based on the intermediary effect of investor confidence on organizations’ financing constraints - Yang, Can; Fang, Zhen; Song, Xiaowei; Liang, Yuhe (Frontiers in Psychology, 2022)
This study examines the impact of digital financing on the degree of financing constraints and discusses the mediating effect of investor confidence. The data are based on companies listed on the Shanghai Stock Exchange and the Shenzhen Stock Exchange from 2010 to 2019. To investigate the impact of digital financing on the financing constraints of companies in different situations, the heterogeneity of internal control and equity characteristics of different organisations is analysed. The results using fixed-effects models show that (i) the change in digital finance has a significant negative impact on the level of corporate financing constraints; (ii) investor confidence plays a mediating role between digital finance and financing constraints; and (iii) the level of internal control impacts the relationship between digital finance and corporate financing constraints. Specifically, for organisations with better internal control, there is a significant negative relationship between digital finance and corporate financing constraints while for organisations with poor internal control, digital finance has no significant influence on the extent of financing constraints; and (iv) digital finance of private organisations is significantly negatively correlated with the extent of financing constraints, while for government organisations, a negative relationship is not evident.